Acute kidney injury in paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) is not associated with progression to chronic kidney disease. Issue 3 (3rd December 2021) - Stewart, Douglas John; Mudalige, Nadeesha Lakmal; Johnson, Mae; Shroff, Rukshana; du Pré, Pascale; Stojanovic, Jelena
Abstract : Background: Paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) is a rare complication of SARS-CoV-2 associated with single or multiorgan dysfunction. Objective: We aimed to evaluate the incidence of acute kidney injury (AKI) and risk factors for kidney dysfunction in PIMS-TS, with reporting of 6-month renal follow-up data. We also evaluated renal involvement between first and second waves of the SARS-CoV-2 pandemic in the UK, the latter attributed to the Alpha variant. Design: A single-centre observational study was conducted through patient chart analysis. Setting: Data were collected from patients admitted to Great Ormond Street Hospital, London, UK, between April 2020 and March 2021. Patients: 110 patients <18 years of age. Main outcome measure: AKI during hospitalisation. AKI classification was based on upper limit of reference interval (ULRI) serum creatinine (sCr) values. Results: AKI occurred in 33 (30%) patients. Hypotension/hypoperfusion was associated with almost all cases. In univariate analysis, the AKI cohort had higher peak levels of triglycerides (OR, 1.27 (95% CI, 1.05 to 1.6) per 1 mmol/L increase) and C reactive protein (OR, 1.06 (95% CI, 1.02 to 1.12) per 10 mg/L increase), with higher requirement for mechanical ventilation (OR, 3.8 (95% CI, 1.46 to 10.4)) and inotropic support (OR, 15.4 (95% CI, 3.02 to 2.81)). In multivariate analysis, triglycerides were independently associated with AKI stages 2–3 (adjusted OR, 1.26 (95% CI, 1.04 to 1.6)). At follow-up, none had macroalbuminuria and all had sCr values <ULRI. No discrepancy in renal involvement between pandemic waves was found. Conclusion: Despite a high incidence of AKI in PIMS-TS, renal recovery occurs rapidly with current therapies, and no patients developed chronic kidney disease. Abstract : Paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (also known as MIS-C) was first described just over one year ago. Data on morbidity and outcome are needed. Acute Kidney Injury occurred in 30% of children in this cohort, but all recovered.